(untitled) (Communications in Computational Physics, 2022)
Many configurations in plasma physics are axisymmetric, it will be more convenient to depict them in cylindrical coordinates compared with Cartesian coordinates. In this paper, a gas-kinetic scheme for collisional Vlasov-Poisson equations in cylindrical coordinates is proposed, our algorithm is based on Strang splitting. The equation is divided into two parts, one is the kinetic transport-collision part solved by multiscale gas-kinetic scheme, and the other is the acceleration part solved by a Runge-Kutta solver. The asymptotic preserving property of whole algorithm is proved and it’s applied on the study of charge separation problem in plasma edge and 1D Z-pinch configuration. Numerical results show it can capture the process from non-equilibrium to equilibrium state by Coulomb collisions, and numerical accuracy is obtained.